F and CF3 substituted solution processable oligo para-phenylenevinylene for ambipolar and hole-transporting organic field effect transistors - Chini, Mrinmoy Kumar; Das, Chayanika; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
We have synthesized benzotrifluoromethyl group substituted para-phenylenevinylene oligomer (denoted as PI) and a cooligomer (denoted as PII) by Gilch polymerization route. The ambipolar field-effect transistor (FET) material PI shows hole and electron mobility 1 x 10 (4) cm(2) V (1) s (1) and 2 x 10 (5) cm(2) V (1) s (1) respectively. PII shows only hole mobility as high as 0.05 cm(2) V (1) s (1) as p-type material. This work highlights the progress of hole-transporting as well as ambipolar material for para-phenylenevinylene derivatives. The results are enlightened on the basis of presence of electronegative substituents and structural modification of the oligomer backbone. (C) 2016 Elsevier B.V. All rights reserved.

Flexible microsupercapacitors using silk and cotton substrates - Das, Chayanika; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2016)
Flexible microsupercapacitors (MSCs) are needed to power ultrasmall wearable electronic devices. Silk cocoons comprise microfibers of silk, which is an attractive natural resource to fabricate MSCs. These fibers are insulators; hence, they must be converted to conducting surfaces. Polyphenols from green tea have been used as a protective layer that also acted as a reducing agent for silver ions. The reduction of silver ions resulted in the formation of silver nanoparticles that subsequently reduced gold ions to gold. The gold film imparts conductivity to the silk fiber without affecting the mechanical strength of the silk fiber. The mechanical strength of uncoated silk fiber and gold coated silk fiber were found to be 5.2 and 5 GPa, respectively. A pseudocapacitive polymer, poly(3,4-ethylenedioxythiophene), was used as the active material to fabricate MSCs. The MSCs showed an impressive gravimetric capacitance of 500 F/g and areal capacitance of 62 mF/cm(2). The power and energy densities were calculated to be 2458 W/kg and 44 Wh/kg, respectively. The device was coiled on a cylinder, and the performance of the device was found to be same as that of the uncoiled device. To demonstrate that the approach is not specific to silk, we also coated gold on cotton fibers using the protocol used to coat gold on silk. Coiled and uncoiled supercapacitors were fabricated using PEDOT coated cotton fibers. The gravimetric capacitance was found to be 250 F/g with energy and power densities of 5.5 Wh/kg and 1118 W/kg, respectively. We have also demonstrated that the devices can be connected in parallel and series to improve the performance of the miniaturized devices.